Reduced circulating BMP9 and pBMP10 in hospitalized COVID‐19 patients. (27th January 2023) - Dunmore, Benjamin J.; Upton, Paul D.; Auckland, Kate; Samanta, Romit J.; Lyons, Paul A.; Smith, Kenneth G. C.; Gräf, Stefan; Summers, Charlotte; Morrell, Nicholas W.
Abstract: Similar to other causes of acute respiratory distress syndrome, coronavirus disease 2019 (COVID‐19) is characterized by the aberrant expression of vascular injury biomarkers. We present the first report that circulating plasma bone morphogenetic proteins (BMPs), BMP9 and pBMP10, involved in vascular protection, are reduced in hospitalized patients with COVID‐19.